Inspecting device, manufacturing device, inspecting method and manufacturing method for wiring board - OKUMURA, HIRONOBU (2011)
An objective is to provide an inspecting device, a manufacturing device, an inspecting method and a manufacturing method for a wiring board capable of enhancing accuracy in inspection. The inspecting device and the manufacturing device for the wiring board comprises: a plurality of jigs where wiring boards are arranged as objects to be inspected; an inspecting portion, performing electrical inspection on the wiring boards arranged on the jigs and determining whether the wiring boards are good or not; a transferring portion, provided with the plurality of jigs and intermittently transferring the jigs to the inspecting portion in sequence; a re-arranging mechanism, re-arranging the wiring board, which is determined defective according to an inspection result of the inspection portion, on another jig which is different from the jig on which the wiring board is arranged when performing the inspection.